Pengaruh Dosis Pupuk NPK dan Zat Pengatur Tumbuh terhadap Kesuburan Tanah, Kadar Fenolik dan Perkembangan Bunga Krisan Pada Dataran Rendah - Refa Firgiyanto; Fadil Rohman; Hanif Fatur Rohman; Leli Kurniasari; Adi Rastono; Ade Sumiahadi; Sinta Dwi Rahma; Mellya Dwi Citra Khysswari (Universitas Gadjah Mada, 2025)
Chrysanthemums (Chrysanthemum spp.) are a floricultural commodity with high economic value and widespread demand as both cut flowers and ornamental plants. However, chrysanthemums generally grow optimally in highlands with cool temperatures, so their cultivation in lowlands faces various physiological constraints, such as decreased flower quality, delayed flowering, and impaired nutrient absorption. This study aimed to evaluate the effects of different NPK fertilizer dosages and types of Plant Growth Regulators (PGRs) on soil nutrient availability (N, P, K), phenolic content, and flowering development of chrysanthemums cultivated in lowlands. The research was conducted in July–October 2024 at the greenhouse of the Jember State Polytechnic Plant Laboratory (±89 m above sea level) using a factorial Completely Randomized Design (CRD) with two factors: NPK 16-16-16 fertilizer dosage (N1 = 4 g/L, N2 = 5 g/L, N3 = 6 g/L) and PGR types (P1 = paclobutrazol, P2 = gaviota, P3 = BAP). The observed variables included soil NPK content, leaf phenolics, flower number, flower diameter, and chlorophyll. The results showed that PGR had a more dominant effect than fertilizer dosage. The N3P3 treatment produced the highest phenolic content (0.257%), while the N1P1 combination increased soil nitrogen accumulation (0.566%), and the N2P3 combination provided the highest phosphorus (0.338%) and potassium (0.190%). The NPK fertilizer dosage did not significantly affect all parameters, while PGR significantly affected the flowering time and flower number. No interaction was found between the two treatment factors.